Entrepreneurship education and training in Malaysia’s public higher learning institutions - Abdul Majid, Izaidin; Cooper, Sarah; Kamarudin, Mohd Fauzi; Ismail, Kamariah (2010)
Enterprise education generally promotes awareness of entrepreneurship in the form of business start-up and self-employment, as well as the usefulness of enterprise skills for competitiveness in the small and large organisations contexts. Specifically, entrepreneurial education is commonly perceived as the process of training individuals to be able to recognize commercial opportunities and the insight, knowledge and related skills to act on them through the formation of a business venture. This paper explores issues pertaining to entrepreneurship education; Malaysia’s Public Higher Learning Institutions (PHLIs) students’ perception towards entrepreneurship education, the prevalence of business start-up tendencies and factors that encourage students to choose to become entrepreneurs upon finishing their studies at the university. The results reveal that a huge majority of the respondents are enthusiastic to the idea of starting their own business. “Attracted with success of other entrepreneurs”, seems to be the most agreed factors that encourage students to become entrepreneurs in future.